Peran Media Sosial Tiktok sebagai Media Pendidikan Hukum untuk Mengembangkan Kompetensi Warga Negara Muda - Kusnadi, Edi; Utami, Amalia (Academy of Education Journal, 2024)
At this time social media is the most popular platform used by teenagers, they use various types of social media, especially Tiktok as a way to entertain themselves when bored and bored. Tiktok is a social media that is widely accessed today because Tiktok not only provides entertainment but also educational benefits. But besides that, there is currently a crisis of legal education shown by the increasing number of law violations by teenagers, this study aims to utilize Tiktok social media, especially on @istilah.law and @harustauhukum.id accounts as legal education media to improve knowledge, attitudes and skills in students at SMA Pendidikan Pembangunan Bangsa Kota Bandung. This study utilizes a qualitative descriptive approach and collects data using questionnaire media, interview techniques, and observation. This research results that Tiktok content on various @istilah.law and @harustauhukum.id accounts that are easy to understand and easily accessible can contribute to increasing knowledge, attitudes and skills